REFLEKSI BIBLIS-TEOLOGIS TERHADAP TEOLOGI FEMINIS (BIBLIS-THEOLOGICAL REFLECTION OF FEMINIST THEOLOGY) - Edi Sugianto; Christian Ade Maranatha (QUAERENS: Journal of Theology and Christianity Studies, 2019)
The fact of the unbalanced treatment of women in various fields has been a struggle for women for centuries. This is the background of the emergence of the women's movement in the 20th century, including feminism, the emancipation of women and women's liberation, which provides a major change for women in modern society. This women's movement presents a new challenge for Christianity, specifically Feminism Theology, which is a theological movement that seeks to form theological vision and reflection through the perspective of oppressed / oppressed women, as a critique of global culture and siding with social justice for women's rights, both within churches and academic institutions and the wider community that tend to be patriarchal. The history of the development of this theology was pioneered by Letty Mandeville Russell; Mary Daly; Rosemary Radford Ruether; Virginia Ramey Mollenkott; and Elizabeth Schüssler Fiorenza. This theology belongs to three groups, namely: radical feminism theology, emancipation and renewal. The challenge raised by this theology is regarding the concept of the Bible, God, Salvation and the Church from exclusively feminist perspective. Based on biblical-theological reflection on the perspective of feminist theology, a new paradigm in the study of the hermeneutics of the Bible is found, namely the perspectives of feminism that may be overlooked, but still prioritize appropriate methods of interpretation so as to provide objective and biblical understanding. Fakta perlakuan terhadap kaum perempuan yang tidak seimbang dalam berbagai bidang telah menjadi pergumulan kaum perempuan selama berabad-abad. Hal tersebut melatar-belakangi munculnya gerakan kaum perempuan pada abad ke-20, di antaranya feminisme, emansipasi perempuan dan women’s liberation, yang memberikan perubahan besar bagi kaum perempuan dalam masyarakat modern. Gerakan perempuan ini memberikan tantangan baru bagi Kristenan, secara khusus Teologi Feminisme, yaitu suatu gerakan teologi yang berusaha membentuk visi dan refleksi teologis melalui sudut pandang perempuan yang tertekan/tertindas, sebagai kritik budaya global dan memihak keadilan sosial bagi hak azasi perempuan, baik di dalam gereja maupun institusi akademis dan masyarakat luas yang cenderung patriarkal. Sejarah perkembangan dari teologi ini dipelopori oleh Letty Mandeville Russell; Mary Daly; Rosemary Radford Ruether; Virginia Ramey Mollenkott; dan Elizabeth Schüssler Fiorenza. Teologi ini tergolong dalam tiga kelompok, yaitu: teologi feminime yang bersifat radikal, emansipasi dan pembaharuan. Adapun tantangan yang dimunculkan oleh teologi ini adalah berkenaan dengan konsep tentang Alkitab, Allah, Keselamatan dan Gereja dari persektif eksklusif feminis. Berdasarkan refleksi biblis-teologi terhadap perspektif teologi feminisme tersebut, maka ditemukan suatu paradigma baru dalam studi hermeneutik Alkitab, yaitu perspekstif feminisme yang mungkin terabaikan, namun tetap mengutamakan metode penafsiran yang tepat sehingga memberikan pemahaman yang objektif dan biblikal.